Synthesis of Chiral Organometallic Salicyloxazoline Complexes: A Novel Perspectives - Luo, Mei; Zhang , Jing Cheng; Yin, Hao; Wang , Cheng Ming; Morris-Natschke, Susan; Lee, Kuo-Hsiung (Novel Aspects on Chemistry and Biochemistry Vol. 2, 2023)
The present study report that chiral salicyloxazoline metal complexes can be produced using 1.0 equiv. of copper, cobalt, nickel, manganese, palladium and platinum salts as the third component. The general strategy for creating metal complexes starts with the synthesis of ligands, which is then followed by ligand reactions with metal salts to produce organometallic complexes. Our research group first reported a one-pot mul-ticomponent synthesis of chiral oxazolinyl-zinc complexes, in the presence of a large amount of ZnCl2 (0.4-2.6 equiv.), with the yields of some products reaching 90%. The prior strategy was extended to use copper, cobalt, nickel, manganese, palladium or platinum salts as the third component. The one-step method used 1.0 equivalent of a metal salt, such as M(OAc)2·nH2O or MCl2·nH2O 2-cyanophenol with different D-and L-amino alcohols. The proposed mechanism indicates that the excess metal salts can activate the reaction of 2-hydroxybenzo-nitrile with d-phenylglycinol in chlorobenzene to form the ligand intermediates and then directly afford the corresponding organometallic complexes via a one-step procedure. Complexes 1-8 were obtained using a one-pot method with a sequential strategy. The reaction out-come was demonstrated for three-component reactions between metal salts, amino alcohols and 2-hydroxybenzoni-trile to afford organometallic complexes in good yields (65-95%). Investigations of the catalytic properties of these complexes as chiral ligands are currently ongoing. These complexes have exhibited bioactivities as anticancer rea-gents, and their future use in medical fields are currently under development.